Peningkatan Prestasi Belajar Matematika Siswa tentang Pengukuran Sudut melalui Demonstrasi, Media Gambar dan Pemberian Tugas Bermakna - Nendah Supriatiningsih (Universitas Indraprasta PGRI, 2018)
Class action: research aims to know the enhancement of student’s mathematics learning achievement after implementing the methods of learning through demonstration, images media and giving meaningful assignment to the students of class V on material about the measurement of the angle. This research was conducted with PTK method in class V SD Negeri 1 Sukamah with the number of students as much as 26. This research was conducted in two cycles. At pre cycle, the average of mathematics mark only 5.3 – under standard KKM. Approximately 50% of the students haven't mastered the material that was given by teacher. After cycle I, there is an enhancement of mathematics mark average, i.e. 6.3. This means that was nearing the criteria of KKM. So that, to improve the learning, it was held cycle II. In this cycle, it's expected that the aims of this study approaching 100%. So it can be concluded that the application of learning method through demonstration, images media, and giving the meaningful assignment can improve learning achievement on the material angle measurement to the students of grade V SD Negeri Sukamanah 1.